AUDIOVISUAL RESOURCES ON THE TEACHING PROCESS IN SURGICAL TECHNIQUE - Guilherme Luiz Lenzi PUPULIM; Rafael Augusto IORIS; Ricardo Ribeiro GAMA; Carmen Australia Paredes Marcondes RIBAS; Osvaldo MALAFAIA; Mirnaluci GAMA (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2015)
Background: The development of didactic means to create opportunities to permit complete and repetitive viewing of surgical procedures is of great importance nowadays due to the increasing difficulty of doing in vivo training. Thus, audiovisual resources favor the maximization of living resources used in education, and minimize problems arising only with verbalism. Aim: To evaluate the use of digital video as a pedagogical strategy in surgical technique teaching in medical education. Methods: Cross-sectional study with 48 students of the third year of medicine, when studying in the surgical technique discipline. They were divided into two groups with 12 in pairs, both subject to the conventional method of teaching, and one of them also exposed to alternative method (video) showing the technical details. All students did phlebotomy in the experimental laboratory, with evaluation and assistance of the teacher/monitor while running. Finally, they answered a self-administered questionnaire related to teaching method when performing the operation. Results: Most of those who did not watch the video took longer time to execute the procedure, did more questions and needed more faculty assistance. The total exposed to video followed the chronology of implementation and approved the new method; 95.83% felt able to repeat the procedure by themselves, and 62.5% of those students that only had the conventional method reported having regular capacity of technique assimilation. In both groups mentioned having regular difficulty, but those who have not seen the video had more difficulty in performing the technique. Conclusion: The traditional method of teaching associated with the video favored the ability to understand and transmitted safety, particularly because it is activity that requires technical skill. The technique with video visualization motivated and arouse interest, facilitated the understanding and memorization of the steps for procedure implementation, benefiting the students performance.